(untitled) (Journal of the Bangladesh Agricultural University, 2011)
An experiment was conducted for two months in a recirculatory system consisting 12 glass aquaria (size 41× 41 × 46 cm) to evaluate the effects of substrates on the growth and survival of Macribrachium rosenbergii postlarvae (PL). Treatment T1 having no substrate was considered as the control. Treatment T2 contained pieces of hollow PVC pipe, treatment T3 and T4 were provided with high density polyethylene (HDPE) and black nylon netting, respectively. Each treatment had three replicates. PL-15 of M. rosenbergii (mean initial length 1.20 ± 0.02 cm; mean initial weight 27 ± 0.02 mg) were stocked at the rate of 75 PLs (1.25 PL L-1) in each aquarium. At the beginning PLs were fed three times daily at the rate of 20% of their body weight which was reduced to 10% at the start of 2nd month. The ranges of water quality parameters recorded in different treatments were: temperature 26 - 29°C; dissolved oxygen 6.2 - 8.1 mg L-1; pH 6.8 - 8.1 and total ammonia 0.01 - 0.15 mg L-1. The result of the study showed that there was no significant difference (P>0.05) in final length of PLs between treatments T3 (HDPE netting) and T4 (nylon netting) but these values were significantly higher than those in T1 (control). There was no significant difference (P>0.05) in final weight and specific growth rates (SGR) of PLs in treatments T3 and T4 but these values were significantly higher than those in T2 (PVC pipe) and T1 (control). Final weights of PLs were 32.70%, 31.54% and 21.05% higher in treatments T3, T4 and T2 respectively than T1 (without substrate). The FCR values ranged between 1.85 and 1.88. There was no significant difference (P>0.05) between the survival of PLs which ranged between 80.33 and 83.00%. Result of the study indicated that growth of M. rosenbergii PLs improved in presence of artificial substrates but the artificial substrates did not improved survival. HDPE and nylon netting gave the best results compared to PVC pipes and control treatments in terms of growth and feed efficiency. Therefore, use of HDPE or nylon netting may be recommended as substrate for successful nursing of M. rosenbergii PLs. However, further studies using different substrates should be carried out in nursery ponds to ascertain the usefulness of these substrates for nursing of M. rosenbergii PLs. Keywords: Nursery rearing; Freshwater prawn; Postlarvae; Artificial substrates DOI: 10.3329/jbau.v8i2.7946 J. Bangladesh Agril. Univ. 8(2): 333-340, 2010